1986
DOI: 10.1016/0167-6636(86)90014-1
|View full text |Cite
|
Sign up to set email alerts
|

Viscoplasticity based on overstress with a differential growth law for the equilibrium stress

Abstract: Two coupled,nonlinear differential equations are proposedfor the modelingof the elasticand rate (time)-dependent inelastic behavior of structural metalsin the absenceof recoveryand aging. The structure of the model is closeto the unifiedtheoriesbut containsessential differences.The properties of the modelare delineated by analytical meansand numericalexperiments.It is shownthat the model reproduces almostelasticregionsupon initialloadingand in the unloading regionsof the hysteresis loop. Under loading,unloadin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(43 citation statements)
references
References 16 publications
1
42
0
Order By: Relevance
“…Most of them were initially used for metals and then extended to polymers. In this category, the Perzyna viscoplasticity theory (Perzyna, 1971) can be used to model the rate-dependent behavior of polymers as demonstrated by Van Der Sluis et al (2001); Kim and Muliana (2010); Abu Al-Rub et al (2015); the viscoplastic theory based on the overstress (VBO) concept (Krempl et al, 1986) can be considered for polymers as shown by Colak (2005); the Bodner and Partom viscoplastic model (Bodner and Partom, 1975) can be applied to polymers as also shown by Frank and Brockman (2001); Zaïri et al (2008). The complex behavior of polymers can thus be captured using a viscoelastic-viscoplastic constitutive model with a robust integration algorithm to be implemented in finite element codes (Miled et al, 2011) by combining a viscoelastic constitutive model with a phenomenological-based viscoplastic one.…”
Section: Introductionmentioning
confidence: 99%
“…Most of them were initially used for metals and then extended to polymers. In this category, the Perzyna viscoplasticity theory (Perzyna, 1971) can be used to model the rate-dependent behavior of polymers as demonstrated by Van Der Sluis et al (2001); Kim and Muliana (2010); Abu Al-Rub et al (2015); the viscoplastic theory based on the overstress (VBO) concept (Krempl et al, 1986) can be considered for polymers as shown by Colak (2005); the Bodner and Partom viscoplastic model (Bodner and Partom, 1975) can be applied to polymers as also shown by Frank and Brockman (2001); Zaïri et al (2008). The complex behavior of polymers can thus be captured using a viscoelastic-viscoplastic constitutive model with a robust integration algorithm to be implemented in finite element codes (Miled et al, 2011) by combining a viscoelastic constitutive model with a phenomenological-based viscoplastic one.…”
Section: Introductionmentioning
confidence: 99%
“…It differs slightly from the formulation given by Krempl et al [1986] and these differences are delineated in the Appendix and in the Appendix of Lee & Krempl [1988].…”
Section: The Uniaxial Version Of Tvbomentioning
confidence: 97%
“…To compare the growth la' 'or tht ,.quilibrium stress in the present theory with one in [Krempl et al, 1986], the t'…”
Section: G J Dvorak and Y Benveniste For Isotropic Constituents Thementioning
confidence: 99%
“…etc. Many other unified cyclic viscoplastic theories were also under development in the same period, using similar concepts, attempting to reconcile cyclic plasticity and creep flow (e.g., refs [42][43][44][45][46]. One advantage of my own approach, mainly based on the very simple structure of the A-F rule, was that it was simple to integrate in closed form (for proportional cyclic conditions) and easily incorporated in a more fundamental thermodynamic framework.…”
Section: Subsequent Developments and Careermentioning
confidence: 99%